The Role of Entrepreneurial Ecosystem in Driving Poverty Reduction in Lesotho - Obiahu, Joseph Echem; Mpundu, Mubanga (Research Collaboration Community (RCC), 2024)
The pervasive nature of poverty across all nations, all ages, all genders, and all races puts continuous search for potential roles of various phenomena in reducing poverty globally at the forefront of academic research effort. This article turns the spotlight on the role of the entrepreneurial ecosystem in driving poverty reduction in Lesotho. It aims to highlight the possible pathways to explore towards the eradication of poverty in the country. We adopted a qualitative research approach to probe the roles of the entrepreneurial ecosystem in releasing individuals wallowing in abject poverty and those vulnerable to poverty. The study identified that by providing access to financing, markets, mentorship, training programmes, and a culture that celebrates risk-taking and problem-solving, the entrepreneurial ecosystem cultivates an atmosphere conducive to the flourishing of small and medium-sized enterprises, thus creating employment opportunities that lift communities out of the cycle of poverty. We discovered that newly created businesses become engines of job creation, providing stable incomes and a pathway to financial security for those previously trapped in poverty. Unfortunately, the study found that most of the components of the entrepreneurial ecosystem fail to discharge the valuable roles effectively in Lesotho due to a number of weaknesses. This study adds to the bundle of academic knowledge and contributes to the effective exploitation of the identified roles in reducing poverty in Lesotho.